Book review: Ghazala Jamil, Accumulation by Segregation: Muslim Localities in Delhi. (May 2018) - Chandola, Tripta
Ghazala Jamil, Accumulation by Segregation: Muslim Localities in Delhi . Delhi: Oxford University Press, 2017, 264 pp., ₹750. ISBN: 9780199470655.